Dampak Kepercayaan dan Kepuasan Nasabah dalam Menggunakan Layanan Perbankan Elektronik BCA Terhadap Loyalitas Nasabah - Grace Mulya Setiabudi; Joshua Boanerges Tampi; Leavy Gaby Jeisy (IPB University, 2023)
The development of information technology has triggered significant changes to various aspects of human life, including the banking industry. The banking industry has adopted electronic banking technology that has made it easier for customers. One of the banks with an excellent reputation for large electronic transactions is Bank BCA. This condition requires Bank BCA always to guarantee the quality of existing electronic services. If the service has problems that interfere with customer satisfaction and trust, Bank BCA has the potential to lose its loyal customers. Therefore, a study was conducted to examine customer trust and satisfaction in using BCA's electronic banking services and their impact on customer loyalty. This study uses a sequential explanatory combination research design, namely a quantitative study first followed by a qualitative study. This method is used to obtain more in-depth data related to the problem under study. The results of this study state that satisfaction has a positive and significant effect on loyalty. However, trust does not affect loyalty. However, this study states that BCA has succeeded in forming customer loyalty, such as the availability to recommend BCA to others, not wanting to switch and open accounts at other banks, and the desire to keep using BCA electronic banking services.